Pengaruh Relaksasi Otot Progresif Terhadap Kualitas Tidur Ibu Hamil Trimester III di Puskesmas Sukamukti Kabupaten Garut Tahun 2024 - Wahyuni, Siti; M, Magdalena; Anggraeni, Milka (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Garut Regency, sleep disorders in pregnant women are around 67% while in Sukamukti Health Center, the incidence of sleep disorders is even higher, reaching 70%. The impact of poor sleep quality is not only felt by the mother, but can also affect the fetus. One way to overcome sleep disorders in pregnant women is progressive relaxation. This technique involves systematic control of muscle tension by calming the mind and body, which can ultimately improve sleep quality. The purpose of the study was to determine the effect of progressive muscle relaxation on the sleep quality of pregnant women in the third trimester. This study used a quasi-experimental with a pre-test - post-test with control group design. The population in the study were all pregnant women in the third trimester with sleep disorders. The number of samples in this study was 36 and was divided into two groups, namely 18 people in the experimental group and 18 people in the control group. Data analysis used the Wilcoxon test. The results of the study obtained the sleep quality of pregnant women in the experimental group before being given the intervention of 13.5 and after being given the intervention became 6.28. In the control group during the first visit it was 13.06 to 12.89 on the second visit. The bivariate results obtained a p-value of 0.000, meaning that there is a significant effect of progressive muscle relaxation on the sleep quality of pregnant women in the third trimester. This study is expected to provide a safe and effective non-pharmacological alternative to improve sleep quality during pregnancy, in addition it is also expected to increase scientific insight into the effectiveness of progressive relaxation techniques in improving sleep quality, especially in pregnant women in the third trimester.